Data, Discoverability, and Translation in the UK and Irish Book Markets - Groenland, Tim; Králová, Michaela (Mémoires du livre / Studies in Book Culture, 2025)
This article explores limitations upon available data on translated books in the UK and Ireland, focusing on the absence of a comprehensive database of titles. Drawing on our investigations and on interviews with publishing professionals, we outline the information gaps and institutional practices that hamper empirical research. We focus on a technical issue that is linked in direct ways to the visibility of writing in translation and translators: namely, the creation and circulation of bibliographical metadata, and the underlying infrastructures through which metadata is shared. We suggest that the discoverability of books in translation—in terms of identifying them as being translated—is directly linked to the extent to which translation and the work of translators are valued by publishers. We then go on to develop this link with respect to literary translators, showing how an absence of information and transparency in the industry defines their working conditions.